EFEKTIVITAS PEMBERIAN EKSTRAK DAUN KELOR (MORINGA OLEIFERA) TERHADAP PENURUNAN TEKANAN DARAH SECARA IN VIVO DAN UJI KLINIS : SYSTEMATIC REVIEW - Rahmanita Kamila Zahra, (2022)
Hypertension or high blood pressure has a prevalence based on Riskesdas in 2018 at the age ≥18 years is 34.1%. Uncontrolled hypertension will cause serious symptoms and complications. Other than using drugs such as beta blockers or ACE inhibitors, herbs is also considered by the community to be alternative medicine such as Moringa leaves (Moringa oleifera). It contain compounds that have an antihypertensive effect such as flavonoids, alkaloids, potassium, and vitamin c. This study aims to determine the compound, effectiveness, and mechanism of Moringa leaf as an antihypertensive. This study used the Systematic Review method by searching literature about the effectiveness of Moringa leaf extract as an antihypertensive based on PRISMA-P, then extracting and synthesizing data on ten selected literatures to be evaluated and concluded. The results of this study include the compounds in Moringa leaf extract such as flavonoid like kaempferol and quercetin, as well as other compounds such as alkaloids, organic acids, steroids, and potassium. Moringa leaf extract can effectively lower blood pressure in animal study with different minimum doses in hypertensive mice and rat. While in clinical trials, giving 250 ml of Moringa leaf decoction for 7 days can effectively reduce blood pressure in hypertensive patients. The mechanism of Moringa leaf extract in lowering blood pressure is as ACE inhibitor, antioxidant, diuretic, and nitric oxide synthase. The conclusion of this study is that the administration of Moringa leaf extract can effectively reduce blood pressure due to the antihypertensive mechanism caused by the phytochemical content in it.